What the EU should do for democracy support in Africa: Ten proposals for a new strategic initiative in times of polarisation - Christine Hackenesch; Julia Leininger; Karina Mross (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
The EU has made democracy support a stronger aspect in its relations with African countries since 2002. However, a broad range of political and economic dynamics within as well as outside of Europe challenge democracy and its supporters: the rise of non-democratic countries such as China, challenges to democracy within the EU, and global autocratization trends, which include African countries. While posing new challenges the EU needs to react to, these trends also reinforce the importance of continued support and protection of democracy abroad. In light of this changed context, the EU will need to fundamentally adjust its strategic approach and instruments towards democracy support in Africa. Against this background, this paper discusses reasons for the EU to continue and even strengthen its democracy support in Africa: societal demands in Africa and regional democracy norms; the relationship between democracy and sustainable development as well as the new geostrategic competition. The paper analyses how the EU's support for democracy and human rights in sub-Saharan Africa has developed over the last decades in terms of its understanding of democracy support as well as its substance. The paper concludes by making ten proposals for reforming the EU's democracy support in Africa. The reform proposals relate to a new narrative and more strategic approach to democracy support in light of the changed geopolitical setting, to addressing megatrends more explicitly through democracy support or to reforming the EU's institutional prerequisites.
Keywords: 330; EU-Außenpolitik; Internationale Beziehungen; Demokratisierung; Subsahara-Afrika; EU-Staaten